The legacy of the «National University of San Marcos» and the learnings of Jürgen Golte - León Gabriel, Doris (2022)
Jürgen Golte was, in his own way, a dissident. But he was not consciously so. His way of doing research was not always a gesture of rebellion or a response to how anthropology was or is being today. However, it was also how he learned to identify interesting topics and then study them reflexively. Perhaps the conjunction of his early training at San Marcos and his German socialization allowed him to develop unrestrained and creative thinking, expressed in his anthropological works, with original findings and his own explanations that responded to the specific societies he interactively approached. He was a self-referential anthropologist, not anchored to simple localist and synchronic descriptions. Throughout his academic life, he was influenced by several authors, assimilating their contributions as resources to analyze the world around him, without overlooking the historical-social character to which the ideas responded, and the contrasts between the moments studied and the moments lived by him.